2002
DOI: 10.1128/jvi.76.7.3365-3373.2002
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackievirus B3 Replication Is Reduced by Inhibition of the Extracellular Signal-Regulated Kinase (ERK) Signaling Pathway

Abstract: Coxsackievirus B3 (CVB3) is the most common human pathogen for viral myocarditis. We have previously shown that the signaling protein p21ras GTPase-activating protein (RasGAP) is cleaved and that mitogenactivated protein kinases (MAPKs) ERK1/2 are activated in the late phase of CVB3 infection. However, the role of intracellular signaling pathways in CVB3-mediated myocarditis and the relative advantages of such pathways to host or virus remain largely unclear. In this study we extended our prior studies by exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
173
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(187 citation statements)
references
References 64 publications
10
173
1
3
Order By: Relevance
“…Recent studies from several laboratories, including our own, indicate that cellular activation and proliferation may be required for productive coxsackievirus infection in tissue culture cells (Feuer et al, 2002;Luo et al, 2002), and viral binding to target cells has been found to stimulate cellular activation via the ERK1/2 (extracellular signal-regulated kinase) pathway (presumably through receptor signaling), which may in turn provide a better cellular setting for viral replication (Luo et al, 2002). In vivo studies correlate with these findings.…”
Section: Discussionsupporting
confidence: 73%
“…Recent studies from several laboratories, including our own, indicate that cellular activation and proliferation may be required for productive coxsackievirus infection in tissue culture cells (Feuer et al, 2002;Luo et al, 2002), and viral binding to target cells has been found to stimulate cellular activation via the ERK1/2 (extracellular signal-regulated kinase) pathway (presumably through receptor signaling), which may in turn provide a better cellular setting for viral replication (Luo et al, 2002). In vivo studies correlate with these findings.…”
Section: Discussionsupporting
confidence: 73%
“…For the replication process, membrane rearrangement utilizing ADP ribosylation factors (Arfs) and guanine nucleotide exchange factors (GEFs) (GBF1, BIG1/2) are required via direct and indirect interaction with viral 3A and 3CD proteins in coxsackievirus B3 (CVB3) and PV infections (Belov et al, 2007;Wessels et al, 2006). Cellular signalling via extracellular signal-regulated kinase (ERK), phosphatidylinositol 3-kinase (PI3K) and stress-activated protein kinases (SAPKs) affected replication and/or the release of progeny virus in CVB3 infection by an unknown mechanism (Esfandiarei et al, 2004;Luo et al, 2002;Si et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, treatment with an inhibitor for PI3K significantly reduced viral RNA synthesis and release of progeny viruses in CVB3 infection (Esfandiarei et al, 2004). In CVB3 infection, a MEK1/2 inhibitor reduced viral protein synthesis and progeny virus release (Luo et al, 2002). Therefore, the MEK/ERK and PI3K/Akt signalling pathways might affect enterovirus infection in different ways depending on the virus species, but seemed to have little effect on PV and EV71 replication, at least by themselves.…”
mentioning
confidence: 99%